Five Years after the Reform of the Social and Unemployment Benefits in Germany - Karl Brenke (Weekly Report, 2010)
Great expectations were connected with the so-called Hartz IV reform which came into effect five years ago. In fact the number of unemployed recipients of Hartz IV benefits drastically went down during the last economic rebound. In earlier economic cycles the number of unemployed recipients of social benefits had stagnated in phases of recovery. But this alone is only a weak sign for success: Firstly, unemployment on the whole decreased more than in previous economic recoveries, and secondly, reentering the labor market is a longer process for Hartz IV recipients than for other unemployed persons. This means that for Hartz IV recipients, the development of worklessness is less linked to the overall economic labor demand than for other unemployed persons. This is partly due to the fact that many of them lack professional training and have only a slim chance to get a new job. Additionally, they often live in areas with considerable labor market problems. Insofar it is indeed a success if unemployment rates drastically went down also for social benefits recipients. There were no significant changes in the willingness to take a job that was offered. The overwhelming majority of unemployed persons was willing to accept a job both before and after the reform. On the whole, Hartz IV recipients are just as willing to work as the rest of the unemployed persons.
Keywords: J64; J65; J68; 330; Labour market reform; Unemployment benefit